Identification of a putative monolignol transporter gene homolog II in Oryza sativa - Ramizan, Muhammad Assiddiq (2015)
Plant cells have sturdy shape because of the presence of cell wall made from three components; cellulose, hemicelluloses, and lignin. Lignin biosynthesis has been studied extensively by many researchers but monolignol transportation process is yet to be explored specifically. It is suggested that monolignol uptakes are dependent towards transport proteins residing in the membrane. AtABCG29 gene of Arabidopsis thaliana codes for a transport protein has been characterized and proven that the protein transports p-coumaryl alcohol. However, the monolignol transport mechanism for Oryza sativa is still elusive. In this study, Oryza sativa‘s gene with locus name OsI_03578 was identified as a putative homologous gene of AtABCG29. OsI_03578 was chosen due to its high sequence similarity with AtABCG29. This research was conducted to investigate whether OsI_03578 gene encodes for a protein that involves in monolignol transportation in Oryza sativa. Total RNA was extracted from Oryza sativa and used to synthesize cDNA which served as a template to amplify OsI_03578 sequence in Oryza sativa. The amplification of the gene sequence was performed by PCR using different sets of primers. In this project, conventional RNA extraction protocol has been optimized and proven to give better RNA yield compared to RNA extraction using commercial kit. However, designation of new primers is necessary in order to amplify specific target region in the gene.